Insect pheromones: An overview of function, form, and discovery. (July 2015) - Yew, Joanne Y.; Chung, Henry
Abstract: For many species of insects, lipid pheromones profoundly influence survival, reproduction, and social organization. Unravelling the chemical language of insects has been the subject of intense research in the field of chemical ecology for the past five decades. Characterizing the forms, functions, and biosynthesis of lipid pheromones has led not only to the development of strategies for controlling agricultural pests but has also provided insights into fundamental questions in evolutionary biology. Despite the enormous variety of chemical structures that are used as pheromones, some common themes in function and biosynthetic pathways have emerged across studies of diverse taxa. This review will offer a general overview of insect lipid pheromone function and biochemical synthesis, describe analytical methods for pheromone discovery, and provide perspectives on the contribution of chemical ecology to pest control and understanding evolutionary processes.